Fine‐mapping of IgE‐associated loci 1q23, 5q31, and 12q13 using 1000 Genomes Project data. Issue 8 (14th June 2014) - Sharma, V.; Michel, S.; Gaertner, V.; Franke, A.; Vogelberg, C.; von Berg, A.; Bufe, A.; Heinzmann, A.; Laub, O.; Rietschel, E.; Simma, B.; Frischer, T.; et al.
Abstract Background Genome‐wide association studies (GWAS) repeatedly identified 1q23 (FCER1A), 5q31 (RAD50‐IL13 and IL4), and 12q13 (STAT6) as major susceptibility loci influencing the regulation of total serum IgE levels. As GWAS may be insufficient to capture causal variants, we performed fine‐mapping and re‐genotyping of the three loci using 1000 Genomes Project datasets. Methods Linkage disequilibrium tagging polymorphisms and polymorphisms of putative functional relevance were genotyped by chip technology (24 polymorphisms) or MALDI‐TOF‐MS (40 polymorphisms) in at least 1303 German children (651 asthmatics). The effect of polymorphisms on total serum IgE, IgE percentiles, and atopic diseases was assessed, and a risk score model was applied for gene‐by‐gene interaction analyses. Functional effects of putative causal variants from these three loci were studied in silico. Results Associations from GWAS were confirmed and extended. For 1q23 and 5q31, the majority of associations were found with mild to moderately elevated IgE levels, while in the 12q13 locus, single‐nucleotide polymorphisms (SNPs) were associated with strongly elevated IgE levels. Gene‐by‐gene interaction analyses suggested that the presence of mutations in all three loci increases the risk for elevated IgE up to fourfold. Conclusion This fine‐mapping study confirmed previous associations and identified novel associations of SNPs in 1q23, 5q31, and 12q13 with different levels of serum IgE and their concomitant contribution to IgE regulation.